2008
DOI: 10.1159/000138915
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Eating Disturbances in Psychiatric Disorders

Abstract: Introduction: Appetite and eating behavior are frequently altered in psychiatric patients. The newly discovered gut-derived neuropeptide ghrelin simulates hunger and weight gain. Therefore, it might be involved in appetite regulation during psychiatric disorders. Methods: In 83 depressed, 42 schizophrenic patients and 46 healthy controls plasma ghrelin levels were measured, and the psychometric scores on the Three-Factor Eating Questionnaire (TFEQ) were assessed. Results: Neither ghrelin levels nor TFEQ scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 46 publications
3
33
2
1
Order By: Relevance
“…In human studies too contrasting findings were reported. Some researches did not find any differences in ghrelin levels between patients with major depression and controls [62,78,79] while other researchers suggested that plasma ghrelin levels as well as preproghrelin mRNA levels are elevated in conditions of stress [77,80] . Ozsoy et al [81] , for example, found higher levels in serum ghrelin levels in depressive patients, than in controls and they also found that high serum ghrelin levels were normalized by treatment.…”
Section: Ref Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…In human studies too contrasting findings were reported. Some researches did not find any differences in ghrelin levels between patients with major depression and controls [62,78,79] while other researchers suggested that plasma ghrelin levels as well as preproghrelin mRNA levels are elevated in conditions of stress [77,80] . Ozsoy et al [81] , for example, found higher levels in serum ghrelin levels in depressive patients, than in controls and they also found that high serum ghrelin levels were normalized by treatment.…”
Section: Ref Findingsmentioning
confidence: 98%
“…Acylation is required for ghrelin to activate its receptor, the growth hormone secretagogue receptor (GHSR). In particular, it promotes food intake and adiposity sending a peripheral signal to the hypothalamus through the neuropeptide Y and agoutirelated protein [62] . Even though AG has a major role in energy balance it also contributes in other biological functions too, such as the regulation of insulin secretion, the regulation of glucose metabolism and influences the pituitary-gonadal axis [63] .…”
Section: Ghrelin's Role In Mood Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these structural findings, elevated leptin levels are associated with reduced cognitive task performance, specifically frontal systems cognitive function [26]. Finally, the orexigenic hormone, ghrelin, is associated with increased disinhibition [31] and negatively correlated with several cognitive domains, including verbal memory, working memory, and naming [25]. Each of these biomarkers also has a demonstrated association with inflammation [32][33][34], and inflammation, in turn, has been linked to dementia including AD [33].…”
Section: Introductionmentioning
confidence: 76%
“…Yapılan çalışmalarda ghrelinin nöroprotektiyonda önemli koruyucu etkisi olduğu bildirilmiştir (25). Literatürde depresif hastalarda düşük (26), yüksek (27) veya değişmeyen ghrelin seviyeleri bildirilmiştir (28). Depresyon hastalarında birbirinden farklı sonuçların bulunması depresyonda ghrelinin rolü ile ilgili bazı tartışmalara neden olmaktadır.…”
Section: Bulgularunclassified